Light‐Triggered Guest Uptake and Release by a Photochromic Coordination Cage1. Issue 4 (3rd December 2012) - Han, Muxin; Michel, Reent; He, Bice; Chen, Yu‐Sheng; Stalke, Dietmar; John, Michael; Clever, Guido H.
<x xml:space="preserve">Abstract</x> A guiding light is sufficient to switch back and forth between the flexible and the stretched, rigid form of a self‐assembled coordination cage based on two square‐planar‐coordinated PdII ions and four ligands with a photochromic dithienylethene (DTE) backbone. The light‐driven interconversion is clean and reversible and allows to control the encapsulation and release of the guest [B12F12]2−.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>